2012
DOI: 10.1007/s00280-012-1828-8
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of melatonin in concurrent chemotherapy or radiotherapy for solid tumors: a meta-analysis of randomized controlled trials

Abstract: Melatonin as an adjuvant therapy for cancer led to substantial improvements in tumor remission, 1-year survival, and alleviation of radiochemotherapy-related side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 27 publications
2
102
0
3
Order By: Relevance
“…The inhibitory action of melatonin on NF-κB leads to an anti-inflammatory and pro-apoptotic effect on cancer cell lines (38,39). Additionally, several meta-analyses support the theory that melatonin administration in patients with cancer is a safe and effective treatment (40,41). These findings support the hypothesis that the mechanism by which melatonin regulates cell growth is affected by the cell type and the concentration of melatonin.…”
Section: Discussionsupporting
confidence: 72%
“…The inhibitory action of melatonin on NF-κB leads to an anti-inflammatory and pro-apoptotic effect on cancer cell lines (38,39). Additionally, several meta-analyses support the theory that melatonin administration in patients with cancer is a safe and effective treatment (40,41). These findings support the hypothesis that the mechanism by which melatonin regulates cell growth is affected by the cell type and the concentration of melatonin.…”
Section: Discussionsupporting
confidence: 72%
“…In the second meta-analysis 8 eligible randomized controlled trials of solid tumor cancers (n=761) were selected [205]. The dosage of melatonin used was 20 mg orally, once a day.…”
Section: Levels Of Amt6s In 12-h Overnight Urine Samplesmentioning
confidence: 99%
“…Still, there is no worldwide consensus on the efficacy of treatment or a reduction in the severity or fewer side effects of the chemotherapy approach [1]. Importantly, a recent meta-analysis indicated that melatonin as an adjuvant therapy for cancer may lead to substantial improvements in tumor remission, 1-year survival, and alleviation of radiochemotherapy-related side effects [2]. Our previous study documents that melatonin inhibits cell proliferation of the human MG-63 osteosarcoma cell line [3].…”
Section: Introductionmentioning
confidence: 99%